Quantitative investigation of the influence of electrode morphology in the electro-chemo-mechanical response of li-ion batteries. (10th February 2022) - Magri, M.; Boz, B.; Cabras, L.; Salvadori, A.
Highlights: We developed quantitative investigations on the influence of electrode morphology in the electro-chemo-mechanical response of Li-ion batteries, stemming from realistic case studies. We implemented the model into an Abaqus 2D/3D code and run complex simulations. We identified limiting factors for battery cells. We identified the relevant role of mechanics in the performance of cells. The model accounts for several fundamental laws, no recourse to electroneutrality is made. Constitutive theory and weak forms are framed in a rigorous PDEs setting. Multiphysics coupling is fully 3D and includes stress analysis. We clarified that, in spite of its complexity, chemo-mechanical-transport and migration cannot suffice to identify the real limiting factors for cells. Abstract: Lithium ion batteries are promising energy storage devices for next generation electric and hybrid vehicles. To achieve high performances and overcome electrochemical deficiencies, significant effort has been made in novel electrode designs and materials. Structural features, such as the morphology of the electrodes, are crucial aspects, too. In this study, we investigate numerically the influence of electrodes architecture, in terms of the electro-chemo-mechanical response of a battery cell with homogeneous electrodes and conventional liquid electrolyte. Simulations predict a suitable design of the electrodes, which leads to major increments of the battery efficiency.